Using the intervention mapping for adaption framework to adapt an evidence-based sexual health intervention for youth affected by trauma - Olivia N. Kachingwe; Quiana Lewis; Asari Offiong; Bianca D. Smith; Ashleigh LoVette; Terrinieka W. Powell (BMC, 2023)
Abstract Background Children exposed to household challenges (i.e., parental substance use, incarceration, and mental illness) are among the groups most vulnerable to sexual risk-taking in adolescence. These behaviors have been associated with a range of negative outcomes later in life, including substance abuse, low educational attainment, and incarceration. Adapting an evidence-based intervention (EBI) to be suitable for this population is one strategy to address the needs of this group. Methods In this study, we describe the use of the Intervention Mapping for Adaption (IM-Adapt) framework to adapt an evidence-based, sexual health intervention (Focus on Youth with Informed Children and Parents). We describe the actions taken at each step of the IM-Adapt process which are to assess needs, search for EBIs, assess fit and plan adaptions, make adaptions, plan for implementation and plan for evaluation. Results Key changes of the adapted intervention include the incorporation of trauma-informed principles and gender inclusive language, standardization of the session length, and modernization of the content to be more appropriate for our priority population. Conclusions The adapted intervention shows promise toward meeting the behavioral health needs of Black youth exposed to household challenges. Our process and approach can serve as a model for researchers and practitioners aiming to extend the reach of EBIs.